2018
DOI: 10.1007/s00423-018-1656-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting morbidity of liver resection

Abstract: In patients undergoing LR, the ACS-NSQIP surgical risk calculator was superior to POSSUM in predicting morbidity risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
0
23
0
2
Order By: Relevance
“…It has been suggested that, in addition to tumor burden, the severity of liver function dysfunction influences treatment options and HCC peri-operative outcomes. 2,3 Worldwide, Child-Pugh (C-P) classification system is widely considered as an important tool to assess preoperative liver function. The C-P grade incorporates serum total bilirubin (TBIL), albumin (ALB), coagulation function, presence of ascites, and hepatic encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that, in addition to tumor burden, the severity of liver function dysfunction influences treatment options and HCC peri-operative outcomes. 2,3 Worldwide, Child-Pugh (C-P) classification system is widely considered as an important tool to assess preoperative liver function. The C-P grade incorporates serum total bilirubin (TBIL), albumin (ALB), coagulation function, presence of ascites, and hepatic encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The patients were scored for ASA physical status classification and referred appropriately to the cardiology or respiratory unit for optimization of comorbidities. Selected patients were offered cardiopulmonary exercise testing, and we determined an anaerobic threshold of < 11 mL/kg/min as a contraindication to HR [12]. The standard operating principles of both open and laparoscopic liver surgery at our unit were published previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, many authors validate their data with existing scoring systems, which were either not designed exclusively for HR in the first place or derived from different patient profiles [11][12][13]. Hence there is a paucity of data with regard to variables predicting 90-day mortality following elective HR for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Hepato-pancreatico-biliary surgery is complex and many units have adopted prehabilitation. In a local study [18] including 245 patients with liver resection the post-operative morbidity, 30-day mortality and 90-day mortality was 38.3%, 2.4% and 3.7% respectively. In a local study [19] including 196 patients with pancreatic resection, the rate of grade B and C post-operative pancreatic fistula, 30-day mortality and 90-day mortality was 5.1%, 0.5% and 2%, respectively.…”
Section: Prehabilitation In Hepato-pancreatico-biliary Surgerymentioning
confidence: 99%
“…One method of patient selection is by virtue of risk prediction. Various risk prediction models are reported in diverse pathologies and surgeries to enhance resource allocation [18,34,35] . A prospective study on 162 patients undergoing hepatopancreaticobiliary surgery by van der Windt et al [36] , showed that scoring systems such as the Risk Analysis Index, was able to accurately predict post-operative outcomes in patients.…”
Section: Target Populationmentioning
confidence: 99%